Elaine Steinbeck by Wing Chong Market - John Bryson:::Creator::::::::::::
Elaine Steinbeck sits in front of the former Wing Chong Market (835 Cannery Row) with two unnamed women. Steinbeck called this Lee Chong's Heavenly Flower Grocery in Cannery Row and Sweet Thursday. Original in safe